CASE REPORT: TREATMENT OF OBLIQUE DIAPHYSIS FEMUR FRACTURE IN A 3-MONTH-OLD LOCAL DOG - Made Vidia Saraswati Devi; I Gusti Agung Gde Putra Pemayun; I Nengah Wandia (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Femoral fracture is damage or loss of continuity of femoral bone tissue with or without displacement of bone fragments. Femoral fractures are often caused by mechanical trauma. A 3-month-old crossbreed dog, weighing 4 kg and male, complained of swelling, unable to walk and the right leg could not support. Based on owner information, the case dog was hit by a vehicle two days earlier. The results of the radiographic examination, the dog had an oblique fracture of the right femoral diaphysis with a prognosis of fausta. Treatment was carried out by surgery using internal fixation of intramedullary pins using general anaesthesia, a combination of xylazine and ketamine. Postoperatively, the antibiotic cefotaxime was given at a dose of 20 mg/kg/q12h (IV), followed by cefadroxil syrup at a dose of 25 mg/kg/q12h analgesic meloxicam tablets at a dose of 0.1 mg/kg/q24h. One week after surgery, a radiographic examination was carried out, the results showed that the pin was pushed up. The second operation was performed to correct the installation of the first pin. After the second operation, the antibiotic amoxicillin syrup (R/Amoxsan) was given at a dose of 20 mg/kgq8h, analgesic mefenamic acid tablets at a dose of 30 mg/kg/q12h and calcium carbonate (R/Osteocal) at a dose of 66 mg/kg/q24h to accelerate the callus formation process. Thirteen days after the operation, the wound had dried well and the dog was able to set its legs and run although it was still limping. The results of the X-Ray radiography thirty-four days after the operation showed that callus had formed on the fracture fragment of the femur bone. It is recommended that surgery be performed immediately to avoid the formation of callus at the end of the fracture and after the installation of the intramedullary pin, periodic radiographic examinations are carried out to determine the position of the pin in the bone marrow.